Seeking the soul: The music of Alfred Schnittke - Odam, George (London Ashgate, 2003)
Alfred Schnittke's music presents a mixture of the old and the new and modernist and post-modernist sounds. It also reflects an eclectic collection of influences. Born in 1934, Schnittke was confined to his native Russia by political necessity but from 1977 became a frequent and welcome visitor to the Western world. He died in 1998 when his international reputation had become well established. With the assistance of Alexander Ivashkin, Director of the Centre for Russian Music, the Guildhall Research Centre has compiled this collection of transcripts of talks given by international experts and papers presented at the Schnittke festival that was held in January 2001. The book is accompanied by a free compact disk containing performances of Schnittke's music played by students at the Guildhall School of Music and Drama.Show More Show Less